How Safe is Your House? - Hal S. Knowles, III; Kathleen C. Ruppert; Karla A. Lenfesty; Barbara Haldeman (EDIS)
ABE-374, a 2-page fact sheet by Hal S. Knowles, III, Kathleen C. Ruppert, Karla A. Lenfesty, and Barbara Haldeman, it part 1 in the Education + Action = Wind Damage Mitigation series. It contains general information about what homeowners can do to protect their property and themselves from windstorms. Published by the UF Department of Agricultural and Biological Engineering, November 2005.